STATUS PERKAWINAN DALAM HUKUM ISLAM: Kajian Teoritik Fiqh Konvensional Dan Fiqh Kontemporer - Sain, Asrizal (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2014)
Islam is a perfect religion (kaamilan). Religion that covers all facets of life. There is not a problem too, in this life,which is not explained. And not a single problem that was not touched on Islamic values , although theseproblems seem small and trivial. That is Islam, the religion which gives mercy to all the worlds. On the issue ofmarriage, indeed islam many mebicarakan problem. Everything has been described in conventional jurisprudenceand contemporary books. From start talking about marriage in Islam to be, to how the practice of life which Islam,Islam led. Similarly, Islam teaches how to realize a family harmony, but still get the blessings and does not violatethe guidance of the Sunnah Prophet sallallaahu ‘alaihi wa sallam, as well as a simple wedding but still full ofcharm.In this short paper will discuss the marriage InsyaAllah according to Islamic law, the legal basis, and theirmarital status described in conventional jurisprudence and contemporary books.[Islam adalah agama yang sempurna (kaamilan). Agama yang mencakup semua sisi kehidupan. Tidakada suatu masalah pun, dalam kehidupan ini, yang tidak dijelaskan. Dan tidak ada satu pun masalahyang tidak disentuh nilai Islam, walau masalah tersebut nampak kecil dan sepele. Itulah Islam, agamayang memberi rahmat bagi sekalian alam. Dalam masalah perkawinan, sungguh Islam banyakmebicarakan masalah itu. Semuanya telah dijelaskan dalam fikih konvensional dan juga fiqhkontemporer. Dari mulai membicarakan perkawinan secara Islam yang sesungguhnya, hinggabagaimana praktek berkehidupan yang Islami, Islam menuntunnya. Begitu pula Islam mengajarkanbagaimana mewujudkan sebuah keluarga yang harmoni, namun tetap mendapatkan berkah dan tidakmelanggar tuntunan sunnah Rasulullah shallallahu ‘alaihi wa sallam, begitu pula dengan pernikahanyang sederhana namun tetap penuh dengan pesona. Dalam makalah yang singkat ini insyaallah akanmembahas perkawinan menurut hukum Islam, dasar hukum, beserta status dalam perkawinan yangdijelaskan dalam fikih konvensional dan fiqh kontemporer.]